2018
DOI: 10.1039/c8gc00744f
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous and rapid preparation of lignin nanoparticles and carbon quantum dots from natural lignocellulose

Abstract: A rapid one-pot microwave-assisted strategy toward the synchronous preparation of two nano-biomaterials with different scales: lignin nanoparticles and carbon nanodots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(64 citation statements)
references
References 48 publications
3
61
0
Order By: Relevance
“…The N‐doped BCDs were prepared to have a size of 19 nm and a quantum yield of up to 46%. N‐doped BCDs were prepared by a one‐step microwave method using natural lignocellulosic as a carbon source in an ethanol–water cosolvent and an acid catalyst system. The prepared BCDs have a diameter distribution ranging from 2 to 3 nm and an average diameter of about 2.6 nm.…”
Section: Methods For the Synthesis Of Bcdsmentioning
confidence: 99%
“…The N‐doped BCDs were prepared to have a size of 19 nm and a quantum yield of up to 46%. N‐doped BCDs were prepared by a one‐step microwave method using natural lignocellulosic as a carbon source in an ethanol–water cosolvent and an acid catalyst system. The prepared BCDs have a diameter distribution ranging from 2 to 3 nm and an average diameter of about 2.6 nm.…”
Section: Methods For the Synthesis Of Bcdsmentioning
confidence: 99%
“…Biomass lignin, an aromatic polymer containing a structural unit of oxyphenylpropanol or its derivatives, is the second mosta bundant naturalm acromolecular organic materiali nt he world. [34][35][36] It has a high carbon content and abundantc hemical energy and is widely presenti ng ymnosperms, angiosperms, and all vascular plants, whereas industrial biomass lignin mainly includes lignosulfonate, sulfate lignin, and alkali lignin. [37][38][39] As an alternative precursor, lignin has been converted to high-valuable nanoscale fluorescent materials in previous work.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that carbon dots could be synthesized from rice straw by a microwave‐assisted one‐pot strategy in an acid‐catalyzed ethanol–water cosolvent system. Moreover, N‐doped carbon dots with 46 % quantum yield and strong purple fluorescence could be obtained by doping nitrogen from protein into the carbon dots during the microwave irradiation process . Shi et al.…”
Section: Bioimagingmentioning
confidence: 99%